Issue Information. Issue 1 (26th March 2019) - Unknown
Abstract : The March issue of PsyCh Journal opens with the special collection on "Altered State of Conciousnes". It features nine contributions: the first two papers consider trait‐mindfulness, i.e. long‐term expertise in contemplative techniques that lead to everyday changes in perception; the next three papers presents altered states of consciousness and selfhood during meditation, hypnosis and the ganzfeld state;one article discloses how dexamphetamine changes timing abilities in healthy individuals; and the final two papers consider time perception in patients with schizophrenia. A number of regular contributions round out the issue, beginning with a psychometric study on the development of Chinese Irrational Beliefs and Rational Attitude Scale (CIBRAS), and another study on autistic traits of special navigation in neurotypical individuals. Next is a psychoimmunological study on the association between hair cortisol levels and symptoms of anxiety and depression among Chinese incarcerated and community adolescents. Finally, an original research article examines whether the processing demand of cues can modulate inhibition of return (IOR) in the detection task. Abstract : The March issue of PsyCh Journal opens with the special collection on "Altered State of Conciousnes". It features nine contributions: the first two papers consider trait‐mindfulness, i.e. long‐term expertise in contemplative techniques that lead to everyday changes in perception; the next three papers presents altered states of consciousness and selfhood during meditation, hypnosis and the ganzfeld state;one article discloses how dexamphetamine changes timing abilities in healthy individuals; and the final two papers consider time perception in patients with schizophrenia. A number of regular contributions round out the issue, beginning with a psychometric study on the development of Chinese Irrational Beliefs and Rational Attitude Scale (CIBRAS), and another study on autistic traits of special navigation in neurotypical individuals. Next is a psychoimmunological study on the association between hair cortisol levels and symptoms of anxiety and depression among Chinese incarcerated and community adolescents. Finally, an original research article examines whether the processing demand of cues can modulate inhibition of return (IOR) in the detection task.